Development and integration of a green roof model within whole building energy simulation - Decruz, Aloysius (2016)
Green roofs are increasingly being employed as a sustainability feature of buildings. The sustainability approach in building designs requires reducing energy consumption and adopting low carbon energy sources without compromising the increasing expectations of comfort and health levels. Given the wide range of building designs, climates and green roof types, it is desirable to evaluate at the design stage the energy saving impact and other potential benefits from the application of green roofs. Currently, the abilities of building simulation programs to simulate the influences of green roofs are limited. For example, they have limitations in representing dynamic inter-layer interactions and moisture infiltration mechanisms. This research aims to develop a new model for the simulation of green roofs based on the control volume approach and to integrate the model within a whole building energy simulation program. The green roof elements consist of special layers such as plants and soil for which the control volume approach is capable of capturing their special characteristics with regards to the thermal and moisture exchanges. The model has been integrated within the ESP-r whole building energy simulation program. Within the ESP-r, the new green roof model alters the boundary condition of a roof surface on which green roof is constructed. The model development is carried out by a series of steps which include a careful selection of governing equations that describe the thermal and moisture balances in various layers of green roof, the numerical implementation for a simultaneous solution of the governing equations for the whole green roof, algorithm and code development and finally developing the interface with ESP-r. After successful integration, the model results were validated on an experimental test cell, which consists of an approximately 2 m2 planted medium on an insulated box with facilities for thermal, moisture and drainage measurements. The results for the thermal validation were promising with the significant boundary temperature values within a root mean square deviation (RMSD) in the vicinity of 0.5 K, whereas the moisture validation results are found to depend on initial conditions, the lower layers showing an RMSD of approximately 0.05 m3/m3 and the top layer nearly 0.12 [m3/m3]. The model is also able to predict the slowing down of water run-off. A methodology for collecting soil and plant properties which are required to be used along with the program has also been described. Based on the current state of the model and also considering the new developments in green roofs, some suggestions are proposed at the end of the thesis as a continuation of this research.